First case of bloodstream infection caused by NDM-positive Escherichia hermannii - Bin Lu; Bin Wang; Xinling Pan; Chenxin Liu; Chenyuan Jin; Yunzhen Shi; Yangxiao Zhou (BMC Infectious Diseases, 2023)
Abstract Background Escherichia hermannii (E. hermanni) is always accompanied by other bacterial infections in humans. In previous reports, most E. hermannii-related infections were caused by sensitive strains. Here, for the first time, we report the case of a patient with New Delhi metallo-β-lactamase (NDM)-positive E. hermannii bloodstream infection. Case presentation The patient was a 70-year-old male admitted to our hospital due to a 4-day fever, with a history of malignant tumor, liver cirrhosis, and chronic obstructive pulmonary disease. After admission, his blood culture tested positive for E. hermannii. The drug resistance analysis showed positive for NDM resistance, with susceptibility to aztreonam, levofloxacin, and amikacin. The blood culture turned negative after 8 days of aztreonam treatment. The patient’s symptoms improved, and he was discharged after 14 days of hospitalization. Conclusions This is the first report of a bloodstream infection caused by an NDM-positive E. hermannii strain. The anti-infection regimen used in this case provides a new reference regimen for clinical practice.